Anxiety, Depression, Stress, Sleep Disorders and Night Eating Syndrome in Adolescents: An Internet Survey - GÜNDOĞDU, ÜMMÜGÜLSÜM (My University, 2023)
This study examined the association between Night Eating Syndrome (NES) problems, sleep disturbances, and the expression of anxiety, depression, and stress in adolescents, taking gender into account. It also investigated whether sleep problems mediate the relationship between NES and anxiety, depression, and stress. This cross-sectional web-based study included 167 adolescents aged 12 to 18 (55.0% girls). Participants completed the self-report Night Eating Questionnaire (NEQ), Scales for Outcomes in Parkinson’s disease (SCOPA) Sleep Scale, and Depression, Anxiety, and Stress Scale–21 items (DASS-21). Increased stress, worsening of depressive symptoms, difficulty falling asleep, and daytime sleepiness were all found to have a significant relationship with NES (p < .05). While higher DASS scores for stress and depression were associated with NEQ > 25 in adolescent girls, higher DASS scores for depression and SCOPA were related in adolescent boys (p < .05). Having trouble falling asleep and feeling sleepy during the day are directly linked to experiencing Night Eating Syndrome (NES). This is mediated both directly and indirectly through symptoms of depression and stress, with statistical significance (p < 0.05). Sleep problems, directly and indirectly, influenced the NES through depression and stress. Reducing depression and stress and addressing sleep problems may help treat NES in adolescents.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)